Predictor-corrector algorithm for pseudo-dynamic testing towards seismic performance evaluation of structures - Kumar, K. Sathish; Jeyasehar, C. Antony; Muthumani, K.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Pseudo-dynamic testing is a hybrid test method for the seismic performance evaluation of structures, which combines the numerical integration of the equations of motion of structure and the experimental measurement of the corresponding restoring forces. In this method the equation of motion is solved on-line, using a step-by-step numerical integration algorithm using the physical restoring forces directly measured from the test specimen and the inertial data from the analytical model. The algorithm broadly used in the pseudo-dynamic test method, essentially is a modifi ed version of Newmark method. A ‘Predictor-Corrector Algorithm’ using a corrective driving parameter, derived from Newmark implicit relations is proposed in the present paper for pseudo-dynamic testing. This algorithm excludes numerical damping, since it is assumed that damping is implicitly taken into account in the experiment on reading the actual restoring forces which are directly measured from the test specimen. The paper presents the genesis, development and mathematical formulation of the predictor-corrector algorithm for pseudo-dynamic testing in detail.